Mensosialisasikan Pentingnya Berpendidikan Tinggi Bagi Perempuan Pada Zaman Modern di Desa Maribaya - Lailatul Ramadhani; Muhamad Rifa’i Subhi (BADAN PENERBIT STIEPARI PRESS, 2024)
In modern times like this, the level of awareness of the importance of education for women is still low. Education is the most important thing in modern times like this. Education is a process of learning knowledge from ignorance to knowledge. Education has changed the world a lot, starting from technology that used to be done manually until now it is all about sophisticated technology, nowadays technology is increasingly developing so it has an impact on education such as the use of gadgets, gadgets that were previously only used to communicate over long distances are now very necessary in the field of education. Moreover, the sophistication of many applications has helped a lot in learning, such as Google Meet, Zoom Meeting and others. However, in Maribaya Village itself there are still many people who think what is the point of a highly educated woman because after marriage a woman works at home, in the kitchen and takes care of the children. However, we look to the future in increasingly modern times, technology is increasingly sophisticated, and women are always required to be capable. Education for women is very important because women will be the first madrassa for their children. Therefore, it is necessary to provide outreach to women in Maribaya village so that they know the importance of education for a woman